PEMANFAATAN FACEBOOK UNTUK PEMASARAN PRODUK USAHA JAHIT RUMAHAN KOTA MADIUN BERBASIS MODEL AIDA - Liris Windyaningrum, Theresia; Ariyani, Vivi; Kurniawati, Dyah (Widya Warta, 2019)
Nowdays, product marketing can be carried out not only with offline which is conventional but also with online using social media for wider marketing coverage. This study aimed to determine the benefits of social media, especially facebook, in the RyzhaModestahome sewing business in raising customer orders and family revenue as well. By using the AIDA model, it was found that in the home sewing business there was any increase in product sales, which was marked by the increasing number of consumer orders.